PJMHS 2022
DOI: 10.53350/pjmhs22168652
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Hypoglycemia in Insulin-Treated Patients of Type 2 Diabetes Mellitus

Abstract: Objective: Our study was designed to explore the frequency of hypoglycemia events in type 2 diabetic patients. We further aimed to correlate the hypoglycemia events with treatment regimes and diabetes duration. Place and Duration: Mayo Hospital Endocrine Outpatient Department. From 1-04-2022 to 30-06-2022. Study type: Clinical based study Methodology: We used the already tested questionnaire from the American Diabetes Association and The Endocrine Society to collect the relevant information. The questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Among the patients surveyed in this study, the leading cause reported for symptomatic hypoglycemia was forgetting to eat, constituting 48.39% of the cases. This result aligns with other research studies conducted by Samya et al (2019) and Shabbir et al (2022), both indicating that the most common cause of hypoglycemia is forgetting to eat, with a percentage of 89.3% [22], [28]. According to patients, most symptomatic hypoglycemic events occurred at unpredictable times (45.16%), followed by daytime (32.26%), and morning (16.13%).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the patients surveyed in this study, the leading cause reported for symptomatic hypoglycemia was forgetting to eat, constituting 48.39% of the cases. This result aligns with other research studies conducted by Samya et al (2019) and Shabbir et al (2022), both indicating that the most common cause of hypoglycemia is forgetting to eat, with a percentage of 89.3% [22], [28]. According to patients, most symptomatic hypoglycemic events occurred at unpredictable times (45.16%), followed by daytime (32.26%), and morning (16.13%).…”
Section: Discussionsupporting
confidence: 91%
“…Among the patients included in the study, those residing in Surabaya exhibited the highest percentage of symptomatic hypoglycemia, accounting for 58.06% of cases. This result is quite different when compared to two different studies, one conducted in a rural area with a prevalence of hypoglycemia at 57.44% [28], and another in an urban area, specifically at Mayo Hospital endocrine, with a prevalence of hypoglycemia in patients with Oral Antidiabetic Drugs (OAD) therapy at 26.39% [22]. According to the author's assumption, this disparity could be due to differences in sample size, where the study conducted at Mayo Hospital involved 360 individuals, allowing for a better distribution of data.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation